O ensino de funções na educação básica - Dias, Valmir Ancelmo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The experience in a school setting (teaching and management) led us to conjecture that any teachers are organized according to the minister are in a given year, considering how prerequisites content taught in previous steps, and often without having any notion of to be worked subsequently. In this thesis, therefore, considering collections of textbooks used in a public school in Cassilândia - MS, we'll show how some concepts related to Function Definition arise in Basic Education. So, we want, in addition to sensitizing the professor of mathematics in relation to the development of a definition, the teacher aware of the need to have general notions of how the mathematical contents are developed in each grade/year of Basic Education, regardless of the series/year effectively he teaches. In other words, we intend to defend the importance of the mathematics teacher to have knowledge of curricular organization of Mathematics of the entire Basic Education and not only the series/year he teaches

A vivência num ambiente escolar (magistério e gestão) nos levou a conjecturar que muitos professores se organizam em função do que devem ministrar em determinado ano, considerando como pré-requisitos conteúdos ministrados em etapas anteriores, e muitas vezes, sem ter noção alguma do que será trabalhado posteriormente. Nesta Dissertação, portanto, considerando coleções de livros didáticos utilizados numa escola pública de Cassilândia - MS, evidenciaremos como alguns conceitos relacionados à Definição de Função surgem na Educação Básica. Assim, pretendemos, além de sensibilizar o professor de Matemática em relação ao desenvolvimento de uma definição, conscientizá-lo da necessidade do mesmo ter noções gerais de como os conteúdos matemáticos são desenvolvidos em cada série/ano da Educação Básica, independente da série/ano que efetivamente leciona. Ou seja, pretendemos defender a importância do professor de Matemática ter conhecimento da organização curricular de Matemática de toda a Educação Básica e não só da série/ano que leciona
Keywords: Matemática - Estudo e ensino; Funções (Matemática) - Estudo e ensino; Educação de base - Mato Grosso do Sul; Livros didáticos; Mato Grosso do Sul - Matemática - Currículos; Mathematics Study and teaching